Linking parental values and infant-mother attachment patterns - Čekuolienė , D. (Psichologija, 1995)
The article emphasizes the aspects of change and socialization of emotional connections. Based on the reviewed literature, the problem of the relationship between the mother ’s values, which are considered to be part of the parents’ values, and the developing attachment type in infancy is raised and analyzed.